(untitled) (Journal of the College of Basic Education, 2026)
The study aimed to identify the impact of the Beyer strategy on the achievement and critical thinking of sixth-grade female students in mathematics. The researcher followed the experimental method with partial control, known as the quasi-experimental method with a post-test. Equivalence was achieved between the control and experimental groups. The study sample consisted of (67) female students. The experimental group, numbering (34) students, studied according to the Beyer strategy, while the control group studied according to the traditional teaching method. The researcher prepared two tests: the first was an achievement test and the second was a critical thinking test. Both items were verified for validity, reliability, and statistical analysis. The results of the study showed that the experimental group, which used the Beyer strategy, outperformed the control group in achievement and critical thinking.